Energy absorption of additively manufactured functionally bi-graded thickness honeycombs subjected to axial loads. (July 2021) - Wu, Yaozhong; Sun, Longfei; Yang, Ping; Fang, Jianguang; Li, Weijia
Abstract: A novel bi-graded honeycomb was proposed by introducing both in-plane and out-of-plane thickness gradients into a regular honeycomb. The graded honeycombs were additively manufactured by fused deposition modeling (FDM) with polylactic acid (PLA) and then tested for axial crushing. Numerical simulation models were constructed through LS-DYNA and validated using experiment results. Based on the super folding element (SFE) method, theoretical models of the proposed bi-graded honeycombs were derived and the accuracy for crushing response was validated against the numerical results. Finally, an active learning based multi-objective optimization algorithm was used to seek the optimal design. The results showed that the bi-graded design for honeycomb structures could improve energy absorption capacity and decrease the peak crushing force in the Pareto frontier manner. The specific energy absorption of the optimal bi-graded honeycomb could be 45.6% higher than that of the regular honeycomb while the peak crushing force was controlled at the same level. Highlights: A bi-graded honeycomb was proposed by introducing two direction thickness gradients. Test specimens were additively manufactured and tested for quasi-static crushing. Theoretical models of the proposed bi-graded honeycomb were built. Optimal design was derived by an active learning based multi-objective optimization.